Functional maxillary orthopedics in early treatment of class II malocclusions due to mandibular retrusion: Case report - Herrera Navarrete, Ivonne Scarlleth; Torres Jiménez, Adriana (Revista Mexicana de Ortodoncia, 2017)
Early treatment of skeletal class II malocclusions with functional orthopedics is a useful means that together with a correct diagnosis, treatment plan and patient cooperation may lead to reducing or eliminating the need for surgery in the future to treat the patient’s problem. Functional orthopedic appliances such as the Bionator promote the adaptive ability of the tissues especially during the early growth spurt and may improve the profile and the skeletal relationship.